2021
DOI: 10.1021/acs.langmuir.1c00726
|View full text |Cite
|
Sign up to set email alerts
|

Droplet Mobility on Slippery Lubricant Impregnated and Superhydrophobic Surfaces under the Effect of Air Shear Flow

Abstract: The focus of this study is to investigate and compare the behavior of a droplet on superhydrophobic (SHS) and slippery lubricant impregnated (SLIPS) surfaces under the effect of air shear flow. In this regard, both experimental and numerical analyses have been conducted to compare their performance on droplet mobility under different air speeds. Two different lubricants have been utilized to scrutinize their effect on droplet movement. The numerical simulations have been performed based on the volume of fluid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…The encrypted region and boundary layer division of the whole computational domain are shown in Figure 5. The dynamic contact angle model used in association with a flow model has been found to be an accurate method to represent the contact angle variation in fluid flow [40]. Thus, the dynamic contact angle is introduced to reproduce the transient contact angle values between the droplet and the wall more accurately.…”
Section: Grid Strategy and Grid Independence Verificationmentioning
confidence: 99%
“…The encrypted region and boundary layer division of the whole computational domain are shown in Figure 5. The dynamic contact angle model used in association with a flow model has been found to be an accurate method to represent the contact angle variation in fluid flow [40]. Thus, the dynamic contact angle is introduced to reproduce the transient contact angle values between the droplet and the wall more accurately.…”
Section: Grid Strategy and Grid Independence Verificationmentioning
confidence: 99%
“…A comprehensive review of recent advances in superhydrophobic surfaces can be found in [70,76]. It is worth noting that there have been only a few experimental and numerical studies conducted to explore how air shear flow influences the droplet dynamics on SHSs [83,84]. In addition, it should be pointed out that when it comes to the impact of micro-scale droplets, the dynamics are different from those at the macro-scale because the surface tension (capillary force) becomes the dominant force over the inertial force.…”
Section: Surface Wetting Static and Dynamic Contact Angle Surface Tex...mentioning
confidence: 99%
“…2020), degreasing cleaning processes (Yeganehdoust et al. 2021) and cell control in microfluidics (Ye, Shen & Li 2018; Minetti et al. 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The deformation and motion of a droplet adhering to a solid wall subject to shear flow is a fundamental phenomenon ubiquitous in industrial and biomedical applications, such as enhanced oil recovery (Rock et al 2020), degreasing cleaning processes (Yeganehdoust et al 2021) and cell control in microfluidics (Ye, Shen & Li 2018;Minetti et al 2019). Over the past few decades, a large number of researches have been carried out on such a topic in Newtonian fluid systems.…”
Section: Introductionmentioning
confidence: 99%